DIGITAL TECHNOLOGIES FOR SUPPORTING THE MANAGEMENT PROCESSES OF TEACHER PROFESSIONAL GROWTH WITHIN THE DEPARTMENTS OF MANAGEMENT IN THE UNIVERSITIES OF THE REPUBLIC OF POLAND - Oliynyk, Victor; Androshchuk, Iryna M. (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
The article examines the possible forms of self-management of the teacher professional growth of the management departments in the universities of the Republic of Poland. The following forms of enhancement of the teacher professional level are analyzed as courses, studies, trainings and portfolio. Distance and open education are characterized as alternative forms of self-management of the teacher professional growth in Polish universities. It was established that teachers of management departments use information systems LMS, LCMS; digital platforms Moodle, ELIAS and USOS in the system of higher education of the Republic of Poland. The types of e-learning are described, its possibilities and influence on the teacher professional growth are characterized within the management departments in the Polish universities. The questionnaires and interviews data are analysed for teachers of management departments in the universities of the Republic of Poland, in which the ways and forms are indicated for self-management of professional growth preferred by the teachers of the management departments of Polish universities. The role of digital technologies is analysed as an integral part in self-management of teacher professional growth in the modern conditions of globalization and European integration of Polish society.